Life, education, history and place of Uzbeks in Afghanistan (Zien Journal of Social Sciences and Humanities, 2023)
In this article, the number of Uzbeks in Afghanistan, the history of Uzbeks in Afghanistan, the difference between the Uzbeks of Uzbekistan and the Uzbeks of Afghanistan, the dialect of the Uzbeks in Afghanistan, the language of the Uzbeks in Afghanistan The place of residence of Uzbeks, some differences between the language of Uzbekistan and the language of Afghanistan, the place of Uzbeks in Afghanistan, and how Uzbeks in Afghanistan are educated in Uzbek are discussed.